Crescimento de Podocarpus lamberti Klotzsch ex Endl. em duas regiões fitogeográficas no estado do Rio Grande do Sul - Milani, Erni José (2010)
In order to study the growth and the relationship with environmental variables of Podocarpus lambertii Klotzsch ex Endl. in two phyto-geographical regions of Rio Grande do Sul state, over hill fields (São Francisco de Paula) and Central depression (São Sepé), four subjects were sampled in each place and went through an complete stern analysis. The results allowed to conclude that the annual increment in diameter presented a positive and significant correlation about the precipitation and relative humidity, indicating that the increase of these variants favors the growth of the diameter. The average temperatures of maximum, absolute maximum, absolute minimal and solar radiation presented significant negative correlations where the increase of these variants represents a tendency of restriction to the growth in diameter. The climate variants explained 25% of the adjust of the annual increment of this species. Some chemical elements of the soil present a positive correlation when related to the periodic annual increment in diameter, urth phosphorum (P), calcium(Ca), magnesium(Mg) and alluminum (Al), explaining 58% of the increment of this species. In São Francisco de Paula, the Podocarpus lambertii presented a maximum diameter of 38.8 cm, in the age of asymptotic of 140 years and, in São Sepé, the maximum diameter was 24.4 cm, in the age of asymptotic of 96 years. The growth in diameter, when compared in the two regions, showed different tendency from 34 years and on, moment when the trees presented the same diameter of 12 cm. From this age, the trees grown in São Francisco de Paula tend to have a higher speed in growth than the ones from São Sepé. Through Backmann s growth of model, using variable dummy 1 (São Francisco de Paula) and dummy 2 (São Sepé), the equations for growing in diameter were obtained, with adjusted coefficient of determination of 0.567 and coefficient of variation of 22.1%; height growing, with coefficient of determination of 0.612 and coefficient of variation of 23.2% and growth in volume, with coefficient of determination of 0.745 and coefficient of variation of 33,2.%.